The Effect of Social Stigmatization on Coping Stress of COVID-19 Survivors Nurses in Handling COVID-19 - Tri Winugroho; I Dewa Ketut Kerta Widana; Mulya Imansyah (International Journal of Indian Psychȯlogy, 2022)
During the Covid-19 pandemic in Indonesia, there was not only an increasing trend in the number of cases, but also a stigma that emerged from the community both to patients and health workers so that it would affect psychologically for health workers in caring for patients. The purpose of this study was to analyze the effects of social stigma on coping stress of Covid-19 Survivors Nurses with stress in handling Covid-19. This study used a correlative quantitative approach with a total sample of 101 nurses at a few hospitals of Central Java Indonesia of Indonesia. The questionnaire method is used as an instrument in data collection and is processed using a Likert scale. Data analysis in this study used the SPSS 20 application to perform statistical tests such as image analysis test, Kolmogorov Smirnov test, hypothesis test, correlation test, regression analysis test. The results of the study can be concluded that with a probability value of p of 0.015 < from the value of α (0.05), this means that in theory h0 is rejected and on the contrary ha is accepted, which means that the emergence of social stigma affects the coping stress of nurses in handling Covid-19.